Pagmatismo pulsional: clínica psicanalítica - Schiavon, João Perci (2012)
The main thesis can be formulated, briefly, as follows: the drive is a practice, an exercise, which may or may not happen it does not occur naturally. This is the origin of its pragmatic value and its ethical consistency. It is a strange formulation considering the idea that the drives are already there, so to speak, as a nature, and that the psyche must be constituted and organized as it controls, dominates, aligns, domesticates, subjugates them and, especially, invests, always through available cultural and symbolic resources. Now, a splitting of the thesis refers to saying that there is a profound difference between the images of the drive, built by not driving bodies, and the driving vision itself. When is it up to the drive and its knowledge? How does it exercise the drive vision? Under what conditions is the drive practiced? And what is the proper time of this practice? These issues are still inside the thesis in question, as still belong to the thesis what we call features of the drive, namely, the features by which the drive or the drives become audible, visible, understandable. The intelligible character of the drive suggests, finally, some logic, the drive logic. Thus we have a drive ethic and a drive logic, a practice and an understanding, with the necessary consequence of conceiving the sublimation as an originating destination from the drive. If this is supported, the split between psyche and the drive should be reviewed, and even what is thought about psychic, when it is seen from a drive perspective. The real, far from being impossible, is not only a matter of experience, as it is a matter of practice. Similarly, the conceptions of order and disorder (or chaos), from the point of view of a psyche, must be rethought. It is not necessary to say that, based on these questions, the concepts of life drive and death drive, including their most critical issues, should also be reviewed. The major interest of this research lies in its practical, clinical - and therefore political, aesthetic... implications. And in what does it invest all the time? In the active character of the analysis.